Challenges in Automated Commercial Aircraft Production. Issue 2 (2022) - Gehlhoff, Felix; Nabizada, Hamied; Weigand, Maximilian; Beers, Lasse; Ismail, Omar; Wenzel, Alexander; Fay, Alexander; Nyhuis, Peter; Lagutin, Wladislav; Röhrig, Martin
Abstract: Civil Aircraft development and production are facing significant challenges in future. On the one hand, the flight-path to carbon neutral aviation, like using liquid hydrogen, will require game changing technologies. Simultaneously, competition, especially on the single aisle market, is evolving fast and puts pressure on market shares and margins. The necessity of an adaptable and highly efficient production becomes more evident than ever. One contribution to achieve this goal is the research project "Intelligent Modular Robotics and Integrated Production System Design for Aircraft Manufacturing" (iMOD). Namely, it will analyze challenges regarding (1) an integrated and Digital Twin-based system design approach, (2) flexible and modular robotics to support workers with unergonomic tasks and (3) a flexible intralogistics based on Automated Guided Vehicles (AGVs). Those three aspects will be integrated into an approach that uses semantic technologies to connect the different components across different levels of functionality and different life cycle phases.